CITRA PEREMPUAN DALAM NOVEL DIA ADALAH KAKAKKU KARYA TERE LIYE - Windha Windha; Martono Martono; Agus Wartiningsih (Universitas Tanjungpura, 2019)
AbstractThis study aims to describe and analyze the image of women found in the novel, Dia Adalah Kakakku by Tere Liye. The method in this study is descriptive, qualitative forms and structural approaches. In this study, the data was obtained through physical and psychological images of a female character in the form of words, phrases, clauses, and sentences from novel. The source of data was the novel Dia Adalah Kakakku by Tere Liye. The technique used is documentary study technique. The data collection tool is the researcher herself as the main instrument. The results of this study are: 1) the physical image of women, included the body, the voice, the eyes, the hair, and the makeup; 2) the psychic image of women, a woman figure who was religious, patient, affectionate, wise, kind, anxiety, excited, weak, touchy, independent, hopeful; and 3) the implementation of the image of women in the novel for learning Indonesian language in terms of aspects of the 2013 curriculum, the objectives of literacy learning, the choice of teaching materials, and aspects of readability were considered valuable for learning materials of class XII students of Senior High. Keywords: The Image of Woman, Novel